Humans who are we? - Armstrong, Jane; Rowley, Christopher; Discovery Channel School (USA: Discovery Channel School, 2003)
See the amazing story of why we're the only species to invest in brains to survive. Unlike animals, we find our source of energy in our minds, not our bodies.
Executive producer, David Lint ; editor, John Whitcher
Narrator: Richard Thomas
Keywords: Human ecology; Human evolution